2006
DOI: 10.3201/eid1210.060495
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Infection in Travelers

Abstract: The largest described outbreak of chikungunya virus has been occurring on the islands of the southwest Indian Ocean since March 2005. We describe the manifestations of chikungunya virus infection in travelers returning from these islands, with focus on skin manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 12 publications
3
78
1
2
Order By: Relevance
“…Upon returning to their native countries these travellers were still positive for the virus [52,53,54]. In Italy, the national infectious diseases surveillance system reported 22 returning travellers with symptoms of CHIKV infection from the Indian Ocean islands (Mauritius, Reunion, Madagascar) between January 2006 and March 2007 who were CHIKV serum positive [54].…”
Section: The Appearance Of Chikungunya Virus In Italy: An Example Of mentioning
confidence: 99%
“…Upon returning to their native countries these travellers were still positive for the virus [52,53,54]. In Italy, the national infectious diseases surveillance system reported 22 returning travellers with symptoms of CHIKV infection from the Indian Ocean islands (Mauritius, Reunion, Madagascar) between January 2006 and March 2007 who were CHIKV serum positive [54].…”
Section: The Appearance Of Chikungunya Virus In Italy: An Example Of mentioning
confidence: 99%
“…Moreover, the first indigenous CHIKV outbreak in Europe was reported from Italy in 2007 (Rezza et al, 2007). Several other European countries (Hochedez et al, 2006;Parola et al, 2006;Veber et al, 2007) and the USA (Lanciotti et al, 2007) have also reported imported infections, raising serious concerns about the potential burden of CHIKV infections.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] For example, chikungunya fever, caused by the alphavirus chikungunya virus, is an emerging infectious disease in endemic and non-endemic regions and can be misdiagnosed as dengue fever, which is largely sympatric in the Old World. [16][17][18][19][20][21] Because the clinical presentation of arboviral disease is often non-specific, reliance on diagnostic testing becomes necessary for accurate differentiation. 22,23 Current laboratory methods are limited by lack of specificity and make conclusive diagnosis difficult.…”
mentioning
confidence: 99%